QTc interval measurement in patients with right bundle branch block: A practical method. Issue 2 (22nd January 2023) - Alizadeh, Abolfath; Shahrbaf, Mohammad Amin; Khorgami, Mohammadrafie; Zeighami, Mahboubeh; Keikhavani, Ala; Mokhtari Torshizi, Hamid; Teimouri‐jervekani, Zahra
Abstract: Background and Aim: Prolonging the QT interval in the right bundle branch block (RBBB) can create challenges for electrophysiologists in estimating repolarization time and eliminating the effect of depolarization changes on QT interval. In this study, we aimed to develop a practice formula to eliminate the effect of depolarization changes on QT interval in patients with RBBB. Methods: This prospective study evaluated accidentally induced RBBB in patients undergoing electrophysiological study. Two expert electrophysiologists recorded the ECG parameters, including QRS duration, QT interval, and cycle length, in the patients. The formula was developed based on QT interval differences (with and without RBBB) and its proportion to QRS. Additionally, the Bazzet, Rautaharju, and Hodge formulas were used to evaluate QTc. Results: We evaluated 96 patients in this study. The mean QT interval without RBBB was 369.39 ± 37.38, reaching 404.22 ± 39.23 after inducing RBBB. ΔQT was calculated as 34.83 ± 17.61, and the ratio of ΔQT/QRS with RBBB was almost 23%. Our formula is: (QTwith RBBB  − 23% × QRS). Subtraction of 25% instead of 23% seems more straightforward and practical. Our formula could also predict the QTc interval in RBBB based on the Bazzet, Rautaharju, and Hodge formulas. Conclusion: Previous formulas for QT correction were hard to apply in the clinical setting or were not specified for RBBB. Our new formula allows a rapid and practical method for QT correction in RBBB in clinical practice. Abstract : The present study introduced a practical formula to determine the QT interval in RBBB. We evaluated 96 patients with accidentally induced RBBB during electrophysiological study. We proposed that Correcting HR with the Hodges, Bazzet, or Rautaharju formulas and subtracting 25% of QRS duration from the QT interval in RBBB seems to predict the actual QTc interval in RBBB.